SMART SOLUTIONS FOR SMALLHOLDER DAIRY FARMS: A MODEL FOR KARAKALPAKSTAN (International Educators Conference, 2025)
This article examines the relevance of smart solutions for smallholder dairy farms in Karakalpakstan. With many producers facing limited resources and poor market access, technologies such as mobile apps, portable cooling units, and digital monitoring systems offer practical tools for improving productivity and quality. The article emphasizes the need for integrated approaches to ensure sustainable development in the region's dairy sector.